1996
DOI: 10.1046/j.1365-2249.1996.d01-775.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies that stabilize the molecular interaction of Ku antigen with DNA-dependent protein kinase catalytic subunit

Abstract: DNA‐dependent protein kinase (DNA‐PK) consists of a DNA binding subunit (Ku autoantigen), and a catalytic subunit (DNA‐PKcs). In the present study, human autoantibodies that recognize novel antigenic determinants of DNA‐PK were identified. One type of autoantibody stabilized the interaction of DNA‐PKcs with Ku and recognized the DNA‐PKcs–Ku complex, but not biochemically purified DNA‐PKcs. Another type recognized purified DNA‐PKcs. Autoantibodies to Ku (p70/p80 heterodimer), ‘stabilizing’ antibodies, and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…* may reflect the presence of a subset of anti-DNA/chromatin Abs (15). These data strongly suggest that pristane enhances/accelerates autoantibody production in a manner different from lpr or gld.…”
Section: Autoantibodies Induced In B6 Mice By Pristane Vs Lpr or Gldmentioning
confidence: 79%
“…* may reflect the presence of a subset of anti-DNA/chromatin Abs (15). These data strongly suggest that pristane enhances/accelerates autoantibody production in a manner different from lpr or gld.…”
Section: Autoantibodies Induced In B6 Mice By Pristane Vs Lpr or Gldmentioning
confidence: 79%
“…The occurrence of autoantibodies in linked sets together with the observation that some autoantibodies tend to stabilize assembled nucleoprotein complexes (5)(6)(7)(8) suggests that the complexes themselves may play an important role in the maintenance and propagation of the autoimmunity. It may be that novel epitopes are formed at protein-nucleic acid interfaces or as the result of conformational changes that accompany complex assembly (9).…”
Section: Identification Of Human Autoantibodies To the Dna Ligase Iv/mentioning
confidence: 99%
“…Subsequent studies using more sensitive techniques revealed the presence of anti-Ku Abs in 5-15% of SLE patients in U.S. populations (16 -18). Abs to another enzyme in the NHEJ pathway, DNA-dependent protein kinase catalytic subunit (DNA-PKcs), have also been detected in SLE patients, and their incidence was shown to be significantly correlated with the presence of anti-Ku autoantibodies (5,19). This suggests that the autoimmune response may be directed in part against an assembled Ku/DNA-PKcs/DNA particle.…”
Section: Identification Of Human Autoantibodies To the Dna Ligase Iv/mentioning
confidence: 99%
“…In the most recent issue of Clinical and Experimental Immunology, Satoh, Reeves and colleagues have provided experimental data that extend the concept of linked autoantibody sets in systemic humoral autoimmunity [15]. They showed that autoantibodies against different protein components of the DNAdependent protein kinase complex (DNA-PK), autoantigenic targets in SLE and other systemic autoimmune diseases, arose in a linked set.…”
Section: Autoimmunogens In Lupus Are Intact Particlesmentioning
confidence: 99%